SOFTWARE SUPPORT FOR MANAGEMENT AND CONTROL OF STUDENTS ACTIVITIES IN THE COMPUTER LAB - DANEK, Jindrich (Trends in education, 2010)
The article deals with one of the ways to effectively manage and monitor activities of students through a sophisticated software designed PC Control. PC control is working through the modules that you can choose the school and used according to their own needs.
Keywords: Software; PC Control; management activities of pupils; monitoring the activities of pupils.